PEMBERIAN TIPS TERHADAP TOUR GUIDE TINJAUAN ETIKA BISNIS ISLAM - Rachman, Dedy Febry; Amri, Syaiful (Valid Jurnal Ilmiah, 2018)
The study was conducted with the aim of describing several issues, including Tipping in a partnership between Art Shop owners and Tour Guide, This research uses descriptive qualitative research design. Research data in the form of exposure in the form of recording of interviews with Art Shop owners and reviewed with Islamic business review. Data collection is done by using interview technique, observation and documentation. The instrument used for data collection in the form of questions submitted to the owner of Art Shop and employees who are deemed to provide the required data. To maintain data validity, data triangulation activities are performed. Data analysis activities started from the data review stage, identification and data classification phase, and data evaluation phase. Based on the results of data analysis, obtained two conclusions of research results as follows.First, the form of cooperation made by the owner of Art Shop and Tour Guide is a form of co-operation of commission. The Tour Guide commission is given when the guest brought by the guide is spending. However, if guests do not spend, Tour Guide only get parking money when using Bus, drink the same cigarette, and this is done by some Art Shop. Cooperation between owner of Art Shop with Tour Guide is oral not written, difficult thing from related institution such as Disperindag and Dispar to prove deviation irregularities that may occur in the matter of oral agreement, so that related institution not know exactly what contents of cooperation between Art Shop and Tour Guide. Second, Provision of commissions in a high percentage is done by Art Shop owners ie there are even up to 50% of the profits of Art Shop owners. But in Islam giving 50% it is not good because it is out of habit, and seen the position of owners of Art Shop and Tour Guide, where Tour Guide is not including the financiers.